The Development of Physics Learning Materials to Improve Students’ Learning Results - Muhammad Syahrul Kahar; Miftah Sigit Rahmawati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2020)
Teaching science should emphasize the provision of real experiences for students to develop their competence so that their ability in learning can be improved. The aim of this study was to evaluate the improvement of students’ learning result after the development of the teaching materials. This study used the Research and Development (R&D) approach with the 4D model. The data were collected through test and validation analysis. The findings show that after teaching implementing the developed material, there were no students in the low category, students in the medium level were 11 (35,48%) only, while the majority of them (20 students) which were 64,52% were categorized into the high level. Besides that, referring to the descriptive analysis of mean scores obtained by students, their achievement was regarded to be better than before (87,06). In terms of the improvement in students’ learning results, after they were taught using the media which was developed in this study, students experienced improvement as the t-test showed the tcount = 50,160 > t table= 2,042 with the significance level of 0,000. Based on that results, the development of teaching material does support the learning activities in the classroom. Therefore, it can be concluded that the use of teaching material brings an impact on the improvement of students’ learning results so that they can understand the materials better. This current study gives insight to the learners about the importance to develop teaching media for learning Physics.